Caribou of the Central Arctic Region of Alaska in relation to adjacent caribou herds - Carruthers, D. R.; Jakimchuk, R. D. (Rangifer, 1986)
There was an unusual increase in numbers of caribou (Rangifer tarandus granti) in the Central Arctic region of Alaska from 1981 to 1985. In fall and winter numbers were up to five times greater than at the onset of calving in June. Numbers appeared to double during the month of June each year, then remain relatively stable over the summer period with a further increase in the fall. Ingress of caribou from outside the region in fall was observed in all years and egress in the early spring is postulated. We conclude that a small resident herd inhabits the region year round with numbers increasing through ingress of caribou from the Western Arctic herd possibly beginning as early as June. Increases or decreases in the size of adjacent herds probably will affect the numbers of caribou occupying the Central Arctic region.